THE EFFECT OF TRAINING AND BALANCE METHOD ON SOCCER SHOOTING IN CANDIDATE MEMBERS OF THE UNITED STATES ACTIVITIES OF THE STUDENTS OF STKIP DHARMA LAMPUNG METRO DISCOURSE (RETEL Journal (Journal on Publication of The Research on Teaching and Language), 2018)
This study aims to determine: differences in the effect between massed practice and distributed practice training methods on soccer shooting results, differences in influence between students who have high dynamic balance and low balance on soccer shooting results, interactions between training methods and dynamic balance students against the results of soccer shooting. This experimental research is factorial 2x1x2. The population of the study was 34 prospective members of the STKIP Dharma Wacana Metro Lampung Football Student Activity Unit. The sample consisted of 20 students who were divided into 4 student groups consisting of 5 students. The sampling technique by combining random purposive sampling. The data analysis technique used was ANAVA test using the SPSS 16.0 program and a significance level of 5%.